IMPLICATURES IN ANGEL LELGA’S UTTERANCES IN MATA NAJWA GENGSI BEREBUT KURSI EPISODE - DIANA, IRIS NADYA VIRDA (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Relevance theory, Explicature, Implicature, Politician By communication, human can share their intention, but sometimes the intention is not communicated explicitly. This kind of communication is called implicature. Implicature conveys intended meaning which can be used by politician as a strategy to vote them. This study deals with the implicature of Angel Lelga, a legislative candidate from Partai Persatuan Pembangunan (PPP) in Mata Najwa talk show program. This study is aimed to analyze: (i) the explicature found in Angel Lelga’s utterances, (ii) the implicated premises found in Angel Lelga’s utterances and (iii) the implicated conclusion found in Angel Lelga’s utterances. In this study, relevance theory which is proposed by Speber and Wilson (1995) is used to analyze the data. This study uses qualitative approach in relation to the use of clear and systematic description about the phenomena being studied. The writer uses content analysis, since the writer analyzes content in transcribed conversation of Angel Lelga in Mata Najwa Talk show. This study reveals that explicit content of Angel Lelga’s utterances are incomplete forms of sentence. From her explicit meaning, hearer creates assumptions which are connected with context of conversation and encyclopaedic knowledge of hearer. To complete inference proceses, hearer takes conclusion from the contextual implication. This study also finds that context and background knowledge are needed in inference processes to get the implicit meaning. From Angel Lelga’s implicature, it can be concluded that she tends to rely on her popularity rather than to focus on explaining her plans or what issue she will be concerned with if she is elected as legislative member.  Finally, it is suggested the next researcher find other forms of communication in different media such as radio or new paper to enrich the study about relevancetheory.